The 'Great Southern Reef': Social, ecological and economic value of Australia's neglected kelp forests - Bennett, Scott; Wernberg, T.; Connell, S.; Hobday, A.; Johnson, C.; Poloczanska, E. (C S I R O Publishing, 2016)
Kelp forests define >8000km of temperate coastline across southern Australia, where ~70% of Australians live, work and recreate. Despite this, public and political awareness of the scale and significance of this marine ecosystem is low, and research investment miniscule (<10%), relative to comparable ecosystems. The absence of an identity for Australia's temperate reefs as an entity has probably contributed to the current lack of appreciation of this system, which is at odds with its profound ecological, social and economic importance. We define the 'Great Southern Reef' (GSR) as Australia's spatially connected temperate reef system. The GSR covers ~71000km2 and represents a global biodiversity hotspot across at least nine phyla. GSR-related fishing and tourism generates at least AU$10 billion year-1, and in this context the GSR is a significant natural asset for Australia and globally. Maintaining the health and ecological functioning of the GSR is critical to the continued sustainability of human livelihoods and wellbeing derived from it. By recognising the GSR as an entity we seek to boost awareness, and take steps towards negotiating the difficult challenges the GSR faces in a future of unprecedented coastal population growth and global change.